Impacts of a bunker levy on decarbonizing shipping: A tanker case study - Lagouvardou, Sotiria; Psaraftis, Harilaos N.; Zis, Thalis (My University, 2022)
The pressure on shipping to reduce its carbon footprint is increasing. Various measures are being proposed at the International Maritime Organization (IMO), including Market-Based Measures (MBMs). This paper investigates the potential of a bunker levy in achieving short-term CO2 emissions reductions. The analysis focuses on the tanker market and uses data from the latest IMO GHG studies and a variety of other sources. The connection between fuel prices and freight rates on the one hand and vessel speeds on the other is investigated for the period 2010–2018. A model to find a tanker's optimal laden and ballast speeds is also developed and applied to a variety of scenarios. Results show that a bunker levy, depending on the scenario, can lead to short-term CO2 emissions reductions of up to 43%. Policy implications are also discussed, particularly vis-à-vis recent IMO and European Union (EU) action on MBMs.
Keywords: GHG emissions; Freight rates; Market-based measures; Shipping decarbonization; IMOBunker levy